Type of physical activity, personal characteristics and muscular strength of older adults in the community (European Journal of Health Research, 2020)
Physical activity is associated with personal performance however, they are considered separate domains of physical function. When the physical activity level is insufficient, the decrease in muscle mass is accelerated. Considering the feminization of aging, it was proposed to analyze the association between different types of physical activity (total physical activity, home, exercise and leisure), personal characteristics, muscle mass and strength in older women in the community. Non-experimental study with descriptivecorrelational design in assistants of three Seniors centers of the office for the Integral Development of the Family. The Physical Activity Scale of the Elderly, Short Physical Performance Battery and bioimpedance analysis were applied. In 200 participants, an inverse association was found between age and muscle mass, strength of upper limbs and physical performance (p.05). The type of physical activity that contributes the least to the total physical activity is the one that is done in free time. Evidence is presented on the differential influence of the physical activity of the home, exercise and age on the muscular strength of older women of the community.